2018
DOI: 10.1021/acs.langmuir.7b03649
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Large Electrolyte Anions on the Sequential Oxidations of Bis(fulvalene)diiron Attached to Glassy Carbon by an Ethynyl Linkage

Abstract: Two ethynyl-derivatized isomers of bis(fulvalene)diiron (BFD, 1,1'-biferrocenylene) were prepared and covalently attached to glassy carbon electrodes through their ethynyl group by three different electrode modification methods. Cyclic voltammetry and square wave (SW) voltammetry were used to characterize surface coverages of 1.4-5.5 × 10 mol cm, the higher of these corresponding to roughly a monolayer, based on computation of an idealized close-packing structure for ethynylbis(fulvalene)diiron (E-BFD) on a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Comparable diminishments of modified electrode currents were observed for all the ferrocenyl systems studied. We noted similar effects for smaller vs larger electrolyte anions in the voltammetry of carbon electrodes modified by attachment of bis(fulvalene)diiron (BFD) through an ethynyl group . In the ethynyl‐BFD case, the differences in the measured peak widths and surface currents became larger in the second oxidation process (in which the dication is formed), but were already observable in the first oxidation process.…”
Section: Resultsmentioning
confidence: 70%
“…Comparable diminishments of modified electrode currents were observed for all the ferrocenyl systems studied. We noted similar effects for smaller vs larger electrolyte anions in the voltammetry of carbon electrodes modified by attachment of bis(fulvalene)diiron (BFD) through an ethynyl group . In the ethynyl‐BFD case, the differences in the measured peak widths and surface currents became larger in the second oxidation process (in which the dication is formed), but were already observable in the first oxidation process.…”
Section: Resultsmentioning
confidence: 70%
“…It was generally observed that the square wave current for the second porphyrin oxidation was smaller than the first (Figure 10), a phenomenon reported previously for the two oxidations of surface-bound ethynylbis(fulvalene)diiron in [B(C 6 F 5 ) 4 ] − -based electrolyte and ascribed to mixed diffusivity of the large counteranion at the solution/surface interface. 73 Brennan et al have also reported examples of overall decreased currents for porphyrin electropolymers in solutions containing large anions. 74 In the present case, comparison with the behavior in smaller-anion electrolytes was not carried out owing to the complication of faster follow-up reactions of [H 2 1] 2+ in small-anion media.…”
Section: Resultsmentioning
confidence: 97%
“…These kind of pre‐waves at the foot of the main wave are not exclusive of the reduction of surface nitrobenzene groups because they were also observed during the reduction of other surface redox groups . In the case of the anodic oxidation of grafted groups like ferrocene, this sort of pre‐waves have not been observed …”
Section: Resultsmentioning
confidence: 98%
“…[11] In the case of the anodic oxidation of grafted groups like ferrocene, this sort of pre-waves have not been observed. [30][31][32] Therefore, the non-ideal behavior of the voltammograms obtained by reduction of the grafted film is related to the generation of nitrobenzene radical anion species, whose stability inside the grafted film can be influenced, in a first approach, by ion-pairing, hydrogen bonding and/or proton transfer processes. The probable intervention of these processes during the reduction of the grafted nitrobenzene moieties represents a high level of complexity and consequently, the intervention of any hydrogen bonding or proton transfer processes promoted by the presence of traces of water in the solvent was minimized using anhydrous acetonitrile and supporting electrolytes purified by recrystallization and dried overnight in an oven at 70°C.…”
Section: Electroactivity Of the Electrografted Nitrophenyl Groupsmentioning
confidence: 99%